Patients’ daily reporting of symptoms via mobile application reveals a significant difference between patients’ perceptions and doctors’ interpretations - Grašič Kuhar, Cvetka; Privšek, Nina; Sraka, Marjetka; Grašič, Ema; Kovač, Timotej; Kukar, Matjaž (Frontiers in Oncology, 2025)
PurposeElectronic patient-reported outcomes (ePROs) are gaining importance. The aim of this study was to investigate the difference in the reporting of symptoms between patients via mobile application (m-app) and doctor assessments. Additionally, usability and satisfaction with the use of the m-app were assessed.MethodsIn this single-center prospective cohort study, we analyzed ePROs in 46 patients receiving (neo)adjuvant chemotherapy for early breast cancer. Patients recorded the occurrence and intensity of symptoms via the Android-based m-app daily. Three-monthly, patients completed validated quality of life questionnaires (EORTC C30 and BR23). For the 10 most common symptoms reported by patients, we compared the frequencies and grades between patients and doctors. Additionally, we compared daily symptom reports with questionnaire results. Finally, the usefulness of and level of satisfaction with the m-app by patients and doctors were evaluated.ResultsDuring the study, patients recorded almost twice as many different symptoms through the m-app as doctors did in the electronic health records (75 vs 49). Symptoms were described by patients as mild (67%), moderate (30%), or severe (3%). The frequency and intensity of symptoms reported by patients were significantly higher than those reported by doctors (p<0.001). Fatigue, insomnia and dry mouth were the three main symptoms reported in more than 75% of patients, but insomnia and dry mouth were also the symptoms most often underreported by doctors. After three months of chemotherapy, QoL assessments revealed worsening of physical, social, cognitive and role functioning, increased fatigue, systemic therapy side effects, and dyspnea but a reduction in arm and shoulder problems. Patients and doctors rated the m-app with an overall score of 4.5 out of 5 (IQR 1.0). Patients expressed high levels of satisfaction with and usability of the m-app. In contrast, doctors were somewhat reluctant to perceive ePROs as an additional burden with patient management.ConclusionThis study revealed a significant discrepancy between patients’ daily symptom reports via the m-app and doctors’ assessments, indicating that healthcare professionals may not fully capture patients’ experiences. This underscores the importance of integrating PROs to accurately evaluate patients’ conditions. Our m-app serves as a promising tool for reporting and managing side effects during systemic treatment of breast cancer.